Implementing and managing remote public service interpreting in response to COVID-19 and other challenges of globalization - René de Cotret, François; Beaudoin-Julien, Andrée-Anne; Leanza, Yvan (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2020)
Although it has been acknowledged that public service interpreting helps reduce the language barriers faced by migrant populations, these barriers continue to be a significant cause of healthcare inequality. With the current COVID-19 pandemic, remote interpreting appears to be the most appropriate solution to address the health inequalities of migrant populations while intervening to reduce the risk of the virus spreading. The purpose of the research was to identify ways of providing a framework for the remote interpretation of public service encounters in the province of Quebec, Canada. A series of recommendations available in the literature were discussed with 27 key actors in the field during focus groups and individual conversations. A thematic analysis of participant discourse allowed us to confirm the extent to which existing recommendations were applicable, to clarify certain recommendations and to add seven new ones. The Guide to the planning and practice of remote public service interpreting (see appendices) consists of 10 recommendations on the planning and management of remote interpreting services and 25 recommendations on the actual encounter. Results show that remote interpreting does not refer solely to telecommunications technology, but also to a knowledge and skill set needed to supervise and coordinate the use of that technology in very specific practice contexts while minimizing the effect of the virtual presence and encouraging the distribution of information among key actors through clearly identified communication channels. The Guide addressed these many features.